Mastering the New Testament ; v. 8 - Dunnam, Maxie D. (Dallas, TX Word, 1982)
Contents : v. 8 : Galatians, Ephesians, Philippians, Colossians, and Philemon. Includes bibliographical references.
Keywords: Bible. N.T. Galatians -- commentaries; Bible. N.T. Ephesians -- commentaries; Bible. N.T. Philippians -- commentaries; Bible. N.T. Colossians -- commentaries; Bible. N.T. Philemon -- commentaries